A Transfer Learning-Based Approach for Classification of Fish Species Using Machine and Deep Learning Techniques. (مجلة الفاروق للعلوم, 2026)
Precise identification of marine fish species is essential to promote sustainable fishery management and preserve marine biodiversity. This research explores the performance of four pre-trained deep learning architectures VGG16, ResNet50, InceptionV3, and MobileNetV2 in a transfer learning paradigm to identify nine marine fish species. A balanced and augmented dataset of 9,000 images (1,000 per species) was employed to promote model generalization and robustness. All the models performed excellently, with ResNet50 recording the highest classification accuracy of 99.72%, followed closely by VGG16 (99.70%), InceptionV3 (99.60%), and MobileNetV2 (99.44%). While overall performance was great, there were minor misclassifications between visually similar species. Model interpretability was enhanced with the Grad-CAM technique, demonstrating that the models effectively attended to relevant morphological features during prediction. Comparing previous work shows that the suggested approach performs better than state-of-the-art models at accuracy even when it is identifying more species. The findings demonstrate the promise of state-of-the-art deep learning for supporting automated, scalable, and accurate marine species classification for environmental and ecological applications.